The zinc finger homeodomain-2 gene of Drosophila controls Notch targets and regulates apoptosis in the tarsal segments. - Guarner, A.; Manjón, C.; Edwards, K.; Steller, H.; Suzanne, M.; Sánchez-Herrero, E. (Developmental Biology, 2014)
The development of the Drosophila leg is a good model to study processes of pattern formation, cell death and segmentation. Such processes require the coordinate activity of different genes and signaling pathways that progressively subdivide the leg territory into smaller domains. One of the main pathways needed for leg development is the Notch pathway, required for determining the proximo-distal axis of the leg and for the formation of the joints that separate different leg segments. The mechanisms required to coordinate such events are largely unknown. We describe here that the zinc finger homeodomain-2 (zfh-2) gene is highly expressed in cells that will form the leg joints and needed to establish a correct size and pattern in the distal leg. There is an early requirement of zfh-2 to establish the correct proximo-distal axis, but zfh-2 is also needed at late third instar to form the joint between the fourth and fifth tarsal segments. The expression of zfh-2 requires Notch activity but zfh-2 is necessary, in turn, to activate Notch targets such as Enhancer of split and big brain. zfh-2 is controlled by the Drosophila activator protein 2 gene and regulates the late expression of tarsal-less. In the absence of zfh-2 many cells ectopically express the pro-apoptotic gene head involution defective, activate caspase-3 and are positive for acridine orange, indicating they undergo apoptosis. Our results demonstrate the key role of zfh-2 in the control of cell death and Notch signaling during leg development.